Provitamin a biofortification in maize through genetic engineering and marker-assisted selection - Thanh, Nguyen Duc (Academia Journal of Biology, 2019)
Maize is an important cereal in the global economy, which feeds one-third of the world’s population and is the third largest food crop after wheat and rice. Nutritional quality of most maize varieties is very low due to the lack of lysine and tryptophan and extremely low provitamin A carotenoids including α-carotene, β-carotene, and β-cryptoxanthin. Therefore, one of the solutions to improve nutritional value in maize is to improve provitamin A carotenoids contents. Many eﬀorts have been made to produce maize plants with enhanced provitamin A carotenoids, especially, β -carotene. This article aims to review the research towards provitamin A biofortification through genetic engineering and marker-assisted selection. The published results and our recent achievements open the window for the improvement of provitamin A carotenoids in maize as well as the issues that need the further investigation.